Esterification and in vitro test of derivatives eugenol from clove (syzygies aromatic) as growth inhibitor of human colorectal cancer cell line HCT-116 - Ongko Joyo, Ericko; Abdurrohman, Hadin; Aditiar Widodo, Vallas; Fadilah, Fadilah; Yazid, Fatmawaty; Arsianty, Ade; Nur Azizah, Norma; Indah Paramita, Rafika (International Journal of Engineering and Technology, 2019)
Colorectal cancer occupies the third position in the world (more than 940,000 cases). Natural compounds are widely used as anti-cancer such as salicylic acid and eugenol isolated from clove (Syzygium aromaticum). The study of the qualitative relationship of eugenol-derived activity structure in the benzene position associated with modification shows that the compound is active as an invitro cancer therapy compound. This research is carried out chemical synthesis by condensation between eugenol and salicylic acid that produce new compound and conducted invitro biological activity test on colorectal cancer cell HCT-116. This research aims to obtaine a new compound derived eugenol that can inhibit the colorectal cancer cell HCT-116. The result of synthesis showed that condensation between eugenol isolates with salicylic acid (ESA) have yield 75% of white needle crystal with melting point 60-65oC. The result of in-vivo test showed that compound ESA have IC50 of 20.98 Â± 2.1 Î¼g / ml and the gossypol standard of natural compounds have IC50 14.22 Â± 1.1 Î¼g / ml. The results of this test indicate that the results of this new compound need to be developed further so have a high potential as a colorectal anticancer compound.Â Â